Labor characteristics and intrapartum interventions in women with vaginal birth after cesarean section - Yehui Lan; Shuangjia Pan; Baoyi Chen; Lingli Peng; Ruyang Chen; Ying Hua; Yanyan Ma (BMC, 2022)
Abstract Background With the development of China's two-child-policy, vaginal birth after cesarean section (VBAC) has aroused public concern. It is important to understand the labour characteristics and intrapartum management of women attempting VBAC to enhance the rates of successful VBAC. The purpose of our research was to investigate the differences in the characteristics of labor, intervention measures and perinatal outcomes between women who had a VBAC and primiparas or multiparas not undergoing VBAC, providing clinical references of intrapartum management for women who are planning a VBAC. Material and methods This observational retrospective study enrolled all women who laboured spontaneously and who had a VBAC (n = 139) at the Second Affiliated Hospital of Wenzhou Medical University in China between 2016 and 2019. They were allocated into VBAC group A (the previous cesarean section was performed before dilation of the cervix) and VBAC group B (the previous cesarean section was performed after dilation of the cervix). The primipara control group included 149 primiparae, and the multipara control group included 155 multiparae with second vaginal birth. Durations of labor, intervention measures and perinatal outcomes were compared among the groups. Results The durations of labor, intrapartum interventions and maternal and neonatal outcomes in VBAC group A were similar to those of the VBAC group B. However, all women who had a VBAC and those in VBAC group A had shorter first, second and the total stages of labor than primiparae. All women with VBAC and those in VBAC group B had longer second stage of labor, but shorter third stage of labor than multiparae. Oxytocin, labor analgesia and artificial rupture of membranes were administered less often in women with VBAC than in primiparae, while phloroglucinol was administered more often in women with VBAC than in multiparae. Women who had a VBAC were more likely to receive episiotomy and had higher incidences of postpartum hemorrhage than primipara and multipara women. Conclusions Labor characteristics, intrapartum interventions and perinatal outcomes in women who had a VBAC with cervical dilation were similar to those in women who had a VBAC without cervical dilation before the previous cesarean section, but differed significantly from those of multiparae and primiparae who did not undergo VBAC.